Qualitative interview study of antibiotics and self-management strategies for respiratory infections in primary care. Issue 11 (26th November 2017) - McDermott, Lisa; Leydon, Geraldine M; Halls, Amy; Kelly, Jo; Nagle, Amanda; White, Jennifer; Little, Paul
Abstract : Objective: To explore perceptions of illness, the decisions to consult and the acceptability of delayed antibiotic prescriptions and self-help treatments for respiratory tract infections (RTIs). Design: Qualitative semistructured interview study. Setting: UK primary care. Participants: 20 adult patients who had been participating in the 'PIPS' (Pragmatic Ibuprofen Paracetamol and Steam) trial in the South of England. Method: Semistructured telephone interviews were conducted with participants to explore their experiences and views on various treatments for RTI. Results: Participants had concerns about symptoms that were not clinically serious and were mostly unaware of the natural history of RTIs, but were aware of the limitations of antibiotics and did not expect them with every consultation. Most viewed delayed prescriptions positively and had no strong preference over which technique is used to deliver the delayed antibiotic, but some patients received mixed messages, such as being told their infection was viral then being given an antibiotic, or were sceptical about the rationale. Participants disliked self-help treatments that involved taking medication and were particularly concerned about painkillers in combination. Steam inhalation was viewed as only moderately helpful for mild symptoms. Conclusion: Delayed prescribing is acceptable no matter how the delay is operationalised, but explanation of the rationale is needed and care taken to minimise mixed messages about the severity of illnesses and causation by viruses or bacteria. Better access is needed to good natural history information, and the signs and symptoms requiring or not requiring general practitioner advice. Significant concerns about paracetamol, ibuprofen and steam inhalation are likely to need careful exploration in the consultation.